Risk Factors of Chronic Atrophic Gastritis - Gontar Alamsyah Siregar; Lydia Imelda Laksmi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Background: Chronic atrophic gastritis is a well-established precursor of gastric cancer. The development of atrophic chronic gastritis is multifactorial, involving the environment as well as host responses to the Helicobacter pylori (H. pylori) infection. The aim of this study is to determine prevalence and risk factors of chronic atrophic gastritis.Method: The study was a cross sectional study on gastritis patients admitted to endoscopy units at Adam Malik General Hospital and Permata Bunda Hospital, Medan, from May-October 2014. A simple random sampling was performed to obtain 50 patients. Data concerning sociodemographic factors and H. pylori status were collected. H. pylori were considered positive from the positive results of the campylobacter like organism (CLO) test. Univariate and bivariate analyses were performed using the SPSS 22 with 95% confidence interval. Bivariat analysis was performed using a Chi-square test. Results: Prevalence of chronic atrophic gastritis was 40%. There were associations between age and chronic atrophic gastritis (95% CI = 1.05-2.80; p = 0.021; OR = 1.73), body mass index and chronic atrophic gastritis (95% CI = 1.1-3.1; p = 0.011; OR = 1.85), and H.pylori infection and chronic atrophic gastritis (95% CI = 1.23-4.88; OR = 2.45; p = 0.001). There were no associations between gender, ethnicity, or rural-urban classification and chronic atrophic gastritis (p 0.05).Conclusion: Elderly status, low BMI, and H. pylori infection are risk factors for the development of chronic atrophic gastritis. Keywords: chronic atrophic gastritis, Helicobacter pylori, gastric atrophy, body mass index